Metodología de diseño para concretos permeables y sus respectivas correlaciones de permeabilidad - Porras-Morales, José Mauricio (Instituto Tecnológico de Costa Rica, 2017)
This project sought to propose a methodology for the design of pervious hydraulic concrete, based on a study of existing design methodologies in other latitudes, where several points were rescued, while others were identified to improve; With this it was possible to propose a design methodology with which, test mixtures were realized varying the relation water/cement and the applied energy of compaction, since these are elements that directly affect the most important characteristics of this concrete as they are the resistance and the associated permeability. The permeable concrete mainly consists of the mixture of hydraulic cement, water and coarse aggregate; Although admixture or a small percentage of fine aggregate may also be included to improve certain properties thereof. Due to its lack or low percentage of fine aggregate, this technology of concrete obtains its particular characteristic of allowing the flow of liquids through it, being this in our area of interest, especially important for the management of runoff water. It was verified that this methodology considered the granulometry of the aggregate, cement characteristics and percentage of voids expected, in addition to the tests that led to find correlations between resistance and permeability.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Cemento; Pavimento poroso; Agua; Resistencia; Construcción; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture